Microbiota in neuroinflammation and synaptic dysfunction: a focus on Alzheimer’s disease - Bairamian, Diane; Sha, Sha; Rolhion, Nathalie; Sokol, Harry; Dorothée, Guillaume; Lemere, Cynthia A.; Krantic, Slavica (Molecular neurodegeneration, 2022)
The implication of gut microbiota in the control of brain functions in health and disease is a novel, currently emerging concept. Accumulating data suggest that the gut microbiota exert its action at least in part by modulating neuroinflammation. Given the link between neuroinflammatory changes and neuronal activity, it is plausible that gut microbiota may affect neuronal functions indirectly by impacting microglia, a key player in neuroinflammation. Indeed, increasing evidence suggests that interplay between microglia and synaptic dysfunction may involve microbiota, among other factors. In addition to these indirect microglia-dependent actions of microbiota on neuronal activity, it has been recently recognized that microbiota could also affect neuronal activity directly by stimulation of the vagus nerve. The putative mechanisms of the indirect and direct impact of microbiota on neuronal activity are discussed by focusing on Alzheimer's disease, one of the most studied neurodegenerative disorders and the prime cause of dementia worldwide. More specifically, the mechanisms of microbiota-mediated microglial alterations are discussed in the context of the peripheral and central inflammation cross-talk. Next, we highlight the role of microbiota in the regulation of humoral mediators of peripheral immunity and their impact on vagus nerve stimulation. Finally, we address whether and how microbiota perturbations could affect synaptic neurotransmission and downstream cognitive dysfunction. There is strong increasing evidence supporting a role for the gut microbiome in the pathogenesis of Alzheimer's disease, including effects on synaptic dysfunction and neuroinflammation, which contribute to cognitive decline. Putative early intervention strategies based on microbiota modulation appear therapeutically promising for Alzheimer's disease but still require further investigation.